Review on Portable Dental Services in Different Regions of America as an Example for Pakistan to Increase Overall Oral Healthcare - Fahad Khan; Aisha Aziz; Mudassir Hussain; Shazia Iqbal; Maraia Saleem (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objective: To assess the reach and effectiveness of mobile dental vans as a delivery method for providing oral healthcare access to people of low socioeconomic status. Methods: A literature review was conducted to identify mobile delivery methods of oral healthcare, the basic aim of which was to address the increasing oral health disparity concern. Forty one articles met the inclusion criteria. Out of the 41 articles, only 7 analysed the coverage and reach of the mobile dental clinics. Data was compiled from the literature in order to assess, evaluate and compare the different mobile dental care delivery methods in dentistry. Results: There is an association between transportation barrier and lack of access to oral healthcare. Thus, mobile dentistry helps deliver dental care to vulnerable populations. Conclusion: Mobile dental clinics are effective methods in improving access to oral healthcare among people of low socioeconomic status, which can be taken as an example for Pakistan in order to increase overall oral healthcare access.